Peningkatan Hasil Belajar Matematika melalui Model Problem Based Learning Berbantu Media Puzzle di Sekolah Dasar - Meinisa, Albi (Pusat Penelitian dan Pengembangan REKARTA, 2019)
The purpose of this research is to improve results of learning mathematic using Problem Based Learning model which helped with puzzle to 5th grade students of SD Negeri Sidorejo Lor 01 Salatiga.The type of this research is Class Action Research (CAR) with a spiral model from C. Kemmis & Mc. Taggart includes planning, implementing actions and observations, and reflection. The research subjects were 5th grade students of SD Negeri Sidorejo Lor 1 Salatiga, totaling 36 students. Data collection techniques using test techniques in the form of evaluation and non-test questions in the form of observation and documentation.The results were evidenced by the average value of mathematics learning outcomes of 5th grade students in pre-cycle was 66.08 with 47.2% learning completeness increased in the first cycle to 76.38 with a completeness percentage of 77.8%. In second cycle it became 86.8 with the percentage of completeness reaching 100% of 36 students. Thus it can be concluded that the learning mathematic using Problem Based Learning model which helped with puzzle can improve results of learning mathematic to 5th grade students of SD Negeri Sidorejo Lor 01 Salatiga.